Geochemical Evaluation and Pore Type Characterization of Carbonaceous Rich Facies in Brown Shale Formation, Central Sumatra Basin - Permana, Asep Kurnia; Iskandar, Yusup (Geological Agency, 2020)
DOI:10.17014/ijog.7.2.121-133Brown Shale Formation of Pematang Group is a key source rock in the Central Sumatra Basin. The formation consists of three lithofacies: algal rich facies, mixed algal-carbonaceous facies, and carbonaceous rich facies. This paper focuses on evaluating the geochemistry and on characterizing the porosity of the carbonaceous rich facies. Geochemical evaluation of the carbonaceous source rocks was conducted using Rock-Eval pyrolysis, while mineralogy and microtextural characterization were assessed by incident light microscopy and scanning electron microscopy (SEM). The results show that the organic components of the carbonaceous source rocks are predominantly composed of vitrinite with minor inertinite and liptinite. The geochemical characteristics indicate that the carbonaceous rich facies could be ranked as a good to excellent level in terms of source rock potential with high TOC content, mainly containing kerogen type III as a gas prone potential. SEM results show that the pore types in the carbonaceous source rocks can be classified into three main types: porous floccules, organic-porosity, and intraparticle pores. Thus, the carbonaceous rich facies of the Brown Shale Formation contains gas prone source rocks with good generation potential, as well as organic rich shale unconventional reservoirs.